2014
DOI: 10.1590/1414-431x20144156
|View full text |Cite
|
Sign up to set email alerts
|

Changes in epidemiology of rotavirus in the Triângulo Mineiro region of Brazil: lack of two consecutive rotavirus seasons

Abstract: Rotaviruses are the main cause of infantile acute diarrhea, and a monovalent (G1P [8]) vaccine against the virus was introduced into the Brazilian National Immunization Program for all infants in March 2006. The objectives of this study were to determine the rate and genotype distribution of rotavirus causing infantile diarrhea in the Triaˆngulo Mineiro region of Brazil during 2011-2012 and to assess the impact of local vaccination. Fecal specimens were analyzed for detection and characterization of rotavirus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
5
0
3
Order By: Relevance
“…Both of these vaccines cover the most common types throughout the world, and are currently in use in several countries. They aim to control severe diarrhea and to prevent death in children younger than 5 years of age [20]. Amongst our strains, 90.2% (55/61) were in the coverage of RotaTeq®, while 67.2% (41/61) were in coverage of Rotarix®.…”
Section: Discussionmentioning
confidence: 92%
“…Both of these vaccines cover the most common types throughout the world, and are currently in use in several countries. They aim to control severe diarrhea and to prevent death in children younger than 5 years of age [20]. Amongst our strains, 90.2% (55/61) were in the coverage of RotaTeq®, while 67.2% (41/61) were in coverage of Rotarix®.…”
Section: Discussionmentioning
confidence: 92%
“…The studies showed that different G-types associated with P[8] co-circulated in 2005 and also that G2P[4] had emerged by mid-2006, continuing as the prevalent genotype until 2010. 7 , 8 , 9 In this study, we characterized the diversity of the VP7, VP4 (VP8* subunit), VP6, NSP4, and NSP5 genes of representative RVA strains that circulated during six seasons (2005–2011) in the TM region.…”
Section: Introductionmentioning
confidence: 99%
“…Rotavirus is member of the genus rotavirus, family Reoviridae, and it is important causative agent of acute gastroenteritis in children and in many young animal species worldwide [1]. There are five species of this virus, referred to as A, B, C, D, and E. Rotavirus A, the most common species, causes more than 90% of infections in humans [2].…”
Section: Introductionmentioning
confidence: 99%